Effectiveness of Giving Ginger Candy to Pregnant Women With Hyperemesis Gravidarum In The First Trimester At The Bontonompo II Gowa Community Health Center - Nurhudayat Trianinsi; Sri Hardiyanti; Awaluddin Awaluddin (Jurnal Gizi dan Kesehatan Keluarga, 2024)
Background: Hyperemesis Gravidarum is excessive nausea and vomiting during pregnancy. This nausea and vomiting can be dangerous for pregnant women because the intensity of the vomiting exceeds that of morning sickness (emesis gravidarum) which occurs early in pregnancy. Nausea and vomiting are physiological things that occur in early pregnancy, but nausea and vomiting that continues to get worse will cause hyperemesis gravidarum which can cause dehydration and acidoketosis. Ginger is a herbal plant that has long been known to prevent nausea and vomiting. Giving ginger candy is effective in reducing the frequency of nausea and vomiting in pregnant women in the first trimester. Objective: To identify the effectiveness of ginger candy against nausea and vomiting in pregnant women who experience hyperemesis gravidarum. Method: This study used the Quasy Experimental research method with a One Group Pretest Posttest design. The sample in this study was 30 pregnant women in the first trimester (0-12 weeks) who experienced nausea and vomiting. Results: The results of this study show that the average value before being given ginger candy was 15.50, while the average value after being given the treatment was 0.00. The results of giving ginger candy to pregnant women with hyperemesis gravidarum in the first trimester are quite effective.